Airtight package

By adding laser absorbing materials to the ceramic substrate and using glass ceramic or alumina materials, combined with laser irradiation technology, the light absorption characteristics of the ceramic substrate and the sealing material layer are solved, and the lack of reactivity between the ceramic substrate and the sealing material layer and the easy glass cover is easy to use. The problem of damage achieves a high airtight reliability and sealing strength of airtight packaging.

CN112640093BActive Publication Date: 2024-12-20NIPPON ELECTRIC GLASS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980058014.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-06
Filing Date
2019-08-21
Publication Date
2024-12-20
Estimated Expiration
2039-08-21

AI Technical Summary

Technical Problem

The ceramic substrate and the sealing material layer are difficult to fully react during laser sealing, resulting in insufficient laser sealing strength, and the glass cover is easily damaged due to thermal impact, which affects the airtight reliability of the airtight packaging.

Method used

By adding 0.1 to 10 mass% of the laser absorbing material to the ceramic substrate, the difference between the light absorption characteristics of the sealing material layer is adjusted, so that the difference between the light absorption rate of the ceramic substrate and the light absorption rate of the sealing material layer is 30 at a wavelength of 808 nm It is preferred that the ceramic matrix is ​​glass ceramic or aluminum oxide material, and a sealing material layer containing glass powder and refractory filler is used, and the sealing material layer is softened and flowed by laser irradiation to achieve airtight integration.

Benefits of technology

The reactivity between the ceramic substrate and the sealing material layer is improved, the laser sealing strength is enhanced, the thermal impact risk of the glass cover is reduced, and the airtight reliability and sealing strength of the airtight sealing body are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112640093B_ABST
    Figure CN112640093B_ABST
Patent Text Reader

Abstract

The airtight package of the present invention is an airtight package formed by airtight integration of a ceramic substrate and a glass cover via a sealing material layer, and is characterized in that the ceramic substrate contains 0.1 to 10 mass % of black pigment, and the difference between the light absorptivity of the ceramic substrate at a wavelength of 808 nm and 0.5 mm and the light absorptivity of the sealing material layer at a wavelength of 808 nm and 0.005 mm is less than 30%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an airtight package, and in particular to an airtight package capable of housing internal components such as LEDs and sensor chips. Background Art

[0002] The airtight package generally includes a light-transmitting glass cover, a ceramic base having a base and a frame provided on the base, and internal components housed in an internal space surrounded by these.

[0003] Internal components such as sensors installed in the airtight package or their peripheral components may be degraded by moisture intruding from the surrounding environment.

[0004] Conventionally, low-temperature curable or ultraviolet curable organic resin adhesives have been used to integrate the ceramic base and the glass cover, but organic resin adhesives are difficult to completely block moisture or gas, and thus may cause internal components to deteriorate over time.

[0005] On the other hand, when the composite powder including the glass powder is used for the sealing material, the internal components are less likely to be degraded by moisture in the surrounding environment.

[0006] However, the softening temperature of glass powder is higher than that of organic resin adhesives, so there is a possibility that internal elements may be thermally degraded during sealing.

[0007] Due to such circumstances, laser sealing has attracted attention. In laser sealing, the sealing material layer is usually irradiated with laser light having a wavelength in the near-infrared region to soften and deform the sealing material layer, thereby airtightly integrating the ceramic substrate and the glass cover. In addition, in laser sealing, only the portion to be sealed can be locally heated, and the ceramic substrate and the glass cover can be airtightly integrated without causing thermal degradation of the internal components.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2013-239609

[0011] Patent Document 2: Japanese Patent Application Publication No. 2014-236202 Summary of the invention

[0012] Problems to be solved by the invention

[0013] However, when laser sealing the ceramic substrate and the glass cover, the ceramic substrate has high thermal conductivity and the temperature of the ceramic substrate is difficult to rise during laser sealing. Therefore, there is a problem that the ceramic substrate and the sealing material layer are difficult to react and it is difficult to ensure the laser sealing strength.

[0014] On the other hand, if the output power of the laser is increased or the scanning speed of the laser is slowed down, the reactivity of the sealing material layer and the ceramic substrate can be improved. However, in this case, a large temperature difference is generated between the locally heated area and the locally unheated area in the glass cover, thereby causing the following problem: the glass cover is easily damaged by thermal shock, thereby making it impossible to ensure the airtight reliability of the airtight package.

[0015] Therefore, the present invention has been made in view of the above circumstances, and a technical object of the present invention is to provide an airtight package having high airtight reliability and high sealing strength.

[0016] Means for solving problems

[0017] The inventors have repeatedly conducted various experiments and found that the technical problem can be solved by reducing the difference in laser absorption characteristics between the ceramic substrate and the sealing material layer, and the present invention is proposed. That is, the airtight package of the present invention is formed by airtight integration of the ceramic substrate and the glass cover through the sealing material layer, and the airtight package is characterized in that: the ceramic substrate contains 0.1 to 10% by mass of laser absorber, and the difference between the light absorption rate of the ceramic substrate converted to 808nm and 0.5mm wavelength and the light absorption rate of the sealing material layer converted to 808nm and 0.005mm wavelength is less than 30%. Here, the so-called "light absorption rate converted to 0.5mm" refers to the light absorption rate when the measured optical path length is set to 0.5mm. For example, even if the thickness of the ceramic substrate is 1.0mm, the measured optical path length is converted to 0.5mm to obtain the light absorption rate. The “0.005 mm converted light absorptivity” refers to the light absorptivity when the measured light path length is 0.005 mm. For example, even when the thickness of the sealing material layer is 0.01 mm, the light absorptivity is calculated by converting the measured light path length to 0.005 mm.

[0018] It should be noted that the light absorption rate is calculated based on Formula 1 by obtaining the total light transmittance and the total light reflectance in a predetermined wavelength range.

[0019] [Formula 1]

[0020] Light absorption rate (%) = {100-(total light transmittance + total light reflectance)} (%)

[0021] In addition, in the airtight package of the present invention, the total light reflectance of the wavelength 808nm and 0.5mm conversion of the preferred ceramic matrix is ​​below 60%. Here, the so-called "total light reflectance of 0.5mm conversion" refers to the total light reflectance when the optical path length is set to 0.5mm, for example, even when the thickness of the ceramic matrix is ​​1.0mm, the optical path length is converted to 0.5mm to obtain the total light reflectance.

[0022] In the airtight package of the present invention, the laser absorber contained in the ceramic base preferably includes at least one selected from Fe-based oxides, Cr-based oxides, Mn-based oxides, Cu-based oxides, and spinel-type composite oxides thereof.

[0023] In the airtight package of the present invention, the ceramic substrate is preferably any one of glass ceramics, alumina, aluminum nitride, or a composite material thereof.

[0024] In the airtight package of the present invention, preferably, the ceramic base has a base and a frame provided on the base, and a sealing material layer is provided between the top of the frame and the glass cover.

[0025] In the airtight package of the present invention, it is preferred that the sealing material layer includes bismuth-based glass containing a transition metal oxide in a glass composition and a refractory filler, and does not substantially contain a laser absorber.

[0026] Furthermore, in the airtight package of the present invention, it is preferable that an internal element is accommodated in the frame portion of the ceramic base.

[0027] Hereinafter, embodiments of the present invention will be described with reference to the drawings. Figure 1 1 is a schematic cross-sectional view of an airtight package of the present invention. The airtight package 1 comprises a glass cover 10 and a ceramic substrate 11. The ceramic substrate 11 comprises a base 12, and further comprises a frame 13 on the outer peripheral edge of the base 12. In addition, an internal component 14 is accommodated in the frame 13 of the ceramic substrate 11. It should be noted that an electrical wiring (not shown) is formed in the ceramic substrate 11 to electrically connect the internal component 14 to the outside.

[0028] A sealing material layer 15 in a frame shape is formed on the surface of the glass cover 10. The width of the sealing material layer 15 is smaller than the width of the top 16 of the frame portion 13 of the ceramic base 11.

[0029] The glass cover 10 and the ceramic base 11 are stacked in such a manner that the center line of the sealing material layer 15 of the glass cover 10 and the top 16 of the frame 13 of the ceramic base 11 in the width direction are aligned. Then, the laser light L emitted by the laser irradiation device 17 is irradiated from the glass cover 10 side along the sealing material layer 15. Thus, after the sealing material layer 15 softens and flows, the glass cover 10 and the ceramic base 11 are hermetically sealed, forming an airtight structure of the airtight package 1. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic cross-sectional view for explaining the form of the airtight package of the present invention. DETAILED DESCRIPTION

[0031] The hermetic sealing package of the present invention preferably has a ceramic substrate, and the ceramic substrate has a base and a frame portion arranged on the base. If so, it is easy to accommodate internal components such as a sensor chip or an LED in the frame portion. The frame portion of the ceramic substrate is preferably formed in a frame shape along the outer peripheral edge portion of the ceramic substrate. If so, the effective area that functions as a device can be expanded. And then it is easy to accommodate internal components such as a sensor chip or an LED in the frame portion of the ceramic substrate, and it is also easy to perform wiring bonding, etc.

[0032] The ceramic substrate contains a laser absorber at a ratio of 0.1 to 10% by mass, preferably 0.2 to 5% by mass. If so, the ceramic substrate can absorb the laser transmitted from the sealing material layer during laser sealing. As a result, the temperature of the interface between the sealing material layer and the ceramic substrate rises, the reactivity of the ceramic substrate and the sealing material layer is improved, and the heat flow to the ceramic substrate side is reduced, so that laser sealing can be performed efficiently.

[0033] From the viewpoint of laser absorption characteristics, the laser absorber includes at least one selected from Fe-based oxides, Cr-based oxides, Mn-based oxides, Cu-based oxides, and spinel-type composite oxides thereof.

[0034] The ceramic substrate is preferably any one of glass ceramic, aluminum oxide, aluminum nitride, or a composite material thereof (for example, a material formed by integrating aluminum nitride and glass ceramic). Glass ceramic can easily form thermal vias, so when the internal components are working, the airtight package can be properly prevented from overheating. Aluminum nitride and aluminum oxide have good heat dissipation properties, so when the internal components are working, the airtight package can be properly prevented from overheating.

[0035] The light absorption rate of the ceramic substrate at a wavelength of 808nm and 0.5mm is preferably 55-95%, 60-90%, and particularly 65-80%. If the light absorption rate of the ceramic substrate at a wavelength of 808nm and 0.5mm is too low, it is difficult to absorb the laser transmitted through the sealing material layer during laser sealing. On the other hand, if the light absorption rate of the ceramic substrate at a wavelength of 808nm and 0.5mm is too high, the heat dissipation of the ceramic substrate is easily reduced due to the excessive content of the laser absorber, and the manufacturing cost of the ceramic substrate is easily increased.

[0036] The difference between the light absorptivity of the ceramic substrate at a wavelength of 808nm and 0.5mm and the light absorptivity of the sealing material layer at a wavelength of 808nm and 0.005mm is 30% or less, preferably 25% or less, 20% or less, 15% or less, 10% or less, and especially 5% or less. If the difference between the light absorptivity of the ceramic substrate at a wavelength of 808nm and 0.5mm and the light absorptivity of the sealing material layer at a wavelength of 808nm and 0.005mm is too large, the laser is excessively absorbed by the sealing material layer during laser sealing, and the temperature of the ceramic substrate is difficult to rise. As a result, the ceramic substrate and the sealing material layer cannot fully react and it is difficult to ensure the laser sealing strength. Or the sealing material layer does not absorb the laser much during laser sealing, and it is difficult for the sealing material layer to soften and flow. As a result, it is difficult to ensure the laser sealing strength.

[0037] The total light reflectance of the ceramic substrate at a wavelength of 808 nm and 0.5 mm is preferably 60% or less, 55% or less, and particularly 50% or less. If the total light reflectance of the ceramic substrate at a wavelength of 808 nm and 0.5 mm is too high, it is difficult to absorb the laser light transmitted through the sealing material layer during laser sealing.

[0038] The thickness of the base portion of the ceramic substrate is preferably 0.1 to 5.0 mm, particularly 0.2 to 1.5 mm, thereby making it possible to reduce the thickness of the airtight package.

[0039] The thickness of the frame of the ceramic base is preferably 0.2 to 5.0 mm, particularly 0.5 to 2.0 mm. This makes it easy to reduce the thickness of the airtight package, and further makes it easy to accommodate internal components such as sensor chips and LEDs, and to perform wiring bonding and the like.

[0040] The width of the frame portion of the ceramic base is preferably 0.3 to 5.0 mm, particularly 0.5 to 4.0 mm. This makes it easy to accommodate internal components and to miniaturize the airtight package.

[0041] The airtight package of the present invention has a glass cover. As the glass cover, various glasses can be used. For example, alkali-free glass, borosilicate glass, and soda-lime glass can be used.

[0042] The thickness of the glass cover is preferably 0.01 to 2.0 mm, 0.1 to 1.2 mm, and particularly 0.3 to 1.0 mm. This can reduce the thickness of the airtight package.

[0043] The functional film may be formed on the surface of the inner element side of the glass cover, or may be formed on the surface of the outer side of the glass cover. As the functional film, an anti-reflection film is particularly preferred. Thus, light reflected on the surface of the glass cover can be reduced.

[0044] The glass cover may be a glass plate laminate formed by laminating and integrating a first glass plate and a second glass plate via an adhesive. Various glasses may be used for the first glass plate and the second glass plate. For example, alkali-free glass, alkali borosilicate glass, and soda-lime glass may be used. It should be noted that the glass plate laminate preferably includes two glass plates, and other plate-like bodies may be further laminated as needed.

[0045] The first glass plate and the second glass plate can be made of the same glass. That is, they can have the same glass composition. In this way, the refractive index, thermal expansion coefficient and other properties of the two plates are consistent, so that the warping of the glass cover or the reflection on the bonding surface can be suppressed.

[0046] In addition, different types of glass can be used for the first glass plate and the second glass plate. That is, they can also have different types of glass compositions. If so, the thermal expansion coefficient of the second glass plate is not restricted by the thermal expansion coefficient of the ceramic substrate, so the thermal expansion coefficients of the ceramic substrate and the first glass plate can be strictly matched, and a cheap glass plate can be used for the second glass plate. As a result, it is easy to take into account both the airtight reliability and manufacturing cost of the airtight package.

[0047] The airtight package of the present invention has a sealing material layer. The sealing material layer is made by coating, drying, removing the binder, and sintering a sealing material paste made by mixing a sealing material with a vehicle liquid. The sealing material is usually a composite powder comprising glass powder and refractory filler powder, and laser absorbers such as coloring pigments are sometimes added as needed. Moreover, the sealing material is a material that softens and flows during laser sealing to integrate the ceramic substrate and the glass cover in an airtight manner. The vehicle liquid usually refers to a mixture of an organic resin and a solvent, that is, a viscous liquid in which an organic resin is dissolved, and the sealing material paste is obtained by dispersing the sealing material in the vehicle liquid. It should be noted that, as needed, a surfactant, a thickener, etc. are sometimes added to the vehicle liquid.

[0048] As a sealing material, a composite powder comprising glass powder and refractory filler powder is preferably used. As a composite powder, a composite powder containing 60 to 100% by volume of glass powder and 0 to 40% by volume of refractory filler powder is preferably used, and a composite powder containing 65 to 95% by volume of bismuth-based glass powder and 5 to 35% by volume of refractory filler powder is further preferably used. Refractory filler powder is added to easily match the thermal expansion coefficients of the ceramic substrate and the glass cover. As a result, it is possible to prevent the situation in which unreasonable stress remains in the sealing area after laser sealing and causes breakage. On the other hand, if the content of refractory filler powder is too much, the content of glass powder becomes relatively less, so the surface smoothness of the sealing material layer is reduced, the adhesion between the top of the frame of the ceramic substrate and the sealing material layer is reduced, and the laser sealing strength is easily reduced.

[0049] The softening point of the sealing material is preferably below 530°C, below 510°C, and especially below 480°C. If the softening point of the sealing material is too high, it is difficult to improve the surface smoothness of the sealing material layer. Furthermore, the temperature needs to be excessively increased during laser sealing, and the glass cover is easily damaged. The lower limit of the softening point of the sealing material is not specifically set. Considering the thermal stability of the glass powder, the softening point of the sealing material is preferably above 350°C. Here, the "softening point" is equivalent to the fourth inflection point when measured by a large DTA device.

[0050] From the viewpoint of improving the laser sealing strength, the glass powder is preferably a bismuth-based glass. The bismuth-based glass preferably contains Bi2O3 28-60%, B2O3 15-37%, ZnO 0-30%, and CuO+MnO (the total amount of CuO and MnO) 1-40% in mole % as a glass composition. The following is an explanation of the reasons for limiting the content range of each component as described above. It should be noted that in the description of the glass composition range, the expression of % refers to mole %.

[0051] Bi2O3 is a main component for lowering the softening point. The content of Bi2O3 is preferably 28-60%, 33-55%, and particularly 35-45%. If the content of Bi2O3 is too little, the softening point is too high and the softening fluidity becomes easily reduced. On the other hand, if the content of Bi2O3 is too much, the glass becomes easily devitrified during laser sealing, and the softening fluidity becomes easily reduced due to the devitrification.

[0052] B2O3 is an essential component as a glass-forming component. The content of B2O3 is preferably 15-37%, 19-33%, and particularly 22-30%. If the content of B2O3 is too low, it becomes difficult to form a glass network, so the glass becomes easily devitrified during laser sealing. On the other hand, if the content of B2O3 is too high, the viscosity of the glass becomes high, and the softening fluidity becomes easily reduced.

[0053] ZnO is a component that improves the resistance to devitrification. The content of ZnO is preferably 0 to 30%, 3 to 25%, 5 to 22%, and particularly 5 to 20%. If the content of ZnO is too high, the components of the glass composition are unbalanced, and the resistance to devitrification tends to decrease.

[0054] CuO and MnO are components that greatly improve laser absorption energy. The combined amount of CuO and MnO is preferably 1-40%, 3-35%, 10-30%, and particularly 15-30%. If the combined amount of CuO and MnO is too little, the laser absorption energy becomes easily reduced. On the other hand, if the combined amount of CuO and MnO is too much, the softening point becomes too high, and even if irradiated with laser, it is difficult for the glass to soften and flow. In addition, the glass becomes thermally unstable and becomes easily devitrified during laser sealing. It should be noted that the CuO content is preferably 1-30%, particularly 10-25%. The MnO content is preferably 0-25%, 1-25%, and particularly 3-15%.

[0055] In addition to the above-mentioned components, for example, the following components may be added.

[0056] SiO2 is a component that improves water resistance. The content of SiO2 is preferably 0-5%, 0-3%, 0-2%, and particularly 0-1%. If the content of SiO2 is too much, the softening point may rise inappropriately. In addition, the glass becomes easily devitrified during laser sealing.

[0057] Al2O3 is a component that improves water resistance. The content of Al2O3 is preferably 0 to 10%, 0.1 to 5%, and particularly 0.5 to 3%. If the content of Al2O3 is too high, the softening point may increase unduly.

[0058] Li2O, Na2O and K2O are components that reduce the devitrification resistance. Therefore, the contents of Li2O, Na2O and K2O are preferably 0 to 5%, 0 to 3%, and particularly preferably 0% or more and less than 1%, respectively.

[0059] MgO, CaO, SrO and BaO are components that improve the devitrification resistance and increase the softening point. Therefore, the contents of MgO, CaO, SrO and BaO are preferably 0 to 20%, 0 to 10%, and particularly 0 to 5%, respectively.

[0060] Fe2O3 is a component that improves devitrification resistance and laser absorption. The content of Fe2O3 is preferably 0-10%, 0.1-5%, and particularly 0.4-2%. If the content of Fe2O3 is too high, the components of the glass composition are unbalanced, and the devitrification resistance tends to decrease.

[0061] Sb2O3 is a component that improves the resistance to devitrification. The content of Sb2O3 is preferably 0 to 5%, particularly 0 to 2%. If the content of Sb2O3 is too high, the components of the glass composition become unbalanced, and the resistance to devitrification tends to decrease.

[0062] In addition, as a sealing material, not only bismuth-based glass but also silver-phosphate-based glass or tellurium-based glass can be used. Compared with bismuth-based glass, silver-phosphate-based glass and tellurium-based glass are easy to soften and flow at low temperatures, and can reduce the thermal strain generated after laser sealing, so they have the characteristics of improving thermal reliability and mechanical reliability. In addition, like bismuth-based glass, silver-phosphate-based glass and tellurium-based glass can improve the mechanical strength of the sealing material layer and reduce the thermal expansion coefficient of the sealing material layer when mixed with refractory filler powder.

[0063] The silver phosphate glass preferably contains, in mol%, 10 to 50% Ag2O, 10 to 35% P2O5, 3 to 25% ZnO, and 0 to 30% transition metal oxide as a glass composition. It should be noted that in the description of the glass composition range of the silver phosphate glass, the expression of % refers to mol %.

[0064] Ag2O is a component that lowers the melting point of glass and makes it difficult to dissolve in water, thereby improving water resistance. The content of Ag2O is preferably 10 to 50%, particularly 20 to 40%. If the content of Ag2O is too low, the viscosity of the glass becomes high, the fluidity becomes easily reduced, and the water resistance becomes easily reduced. On the other hand, if the content of Ag2O is too high, vitrification is difficult.

[0065] P2O5 is a component that lowers the melting point of glass. Its content is preferably 10 to 35%, particularly 15 to 25%. If the content of P2O5 is too low, vitrification is difficult. On the other hand, if the content of P2O5 is too high, weather resistance and water resistance are easily reduced.

[0066] ZnO is a component that improves devitrification resistance, and its content is preferably 3 to 25%, 5 to 22%, and particularly 9 to 20%. If the ZnO content is outside the above range, the component balance of the glass composition is impaired, and devitrification resistance is likely to decrease.

[0067] The transition metal oxide is a component having laser absorption properties, and its content is preferably 0 to 30%, 1 to 30%, and particularly 3 to 15%. If the content of the transition metal oxide is too high, the devitrification resistance tends to decrease.

[0068] If CuO is added, laser absorption characteristics can be improved. The content of CuO is preferably 0 to 30%, 1 to 30%, and particularly 3 to 15%. If the content of CuO is too high, the component balance of the glass composition is impaired, and the devitrification resistance tends to decrease.

[0069] In addition to the above-mentioned components, for example, the following components may be added.

[0070] TeO2 is a glass-forming component and a component that lowers the melting point of glass. The content of TeO2 is preferably 0 to 40%, particularly 10 to 30%.

[0071] Nb2O5 is a component that improves water resistance. The content of Nb2O5 is preferably 0 to 25%, particularly 1 to 12%. If the content of Nb2O5 is too high, the viscosity of the glass increases and the fluidity tends to decrease.

[0072] Li2O, Na2O and K2O are components that reduce the devitrification resistance. Therefore, the contents of Li2O, Na2O and K2O are 0 to 5%, 0 to 3%, and particularly 0% or more and less than 1%, respectively.

[0073] MgO, CaO, SrO and BaO are components that improve the devitrification resistance and increase the softening point. Therefore, the contents of MgO, CaO, SrO and BaO are 0 to 20%, 0 to 10%, and particularly 0 to 5%, respectively.

[0074] The tellurium-based glass preferably contains TeO2 20-80%, Nb2O 50-25%, and transition metal oxide 0-40% as a glass composition in terms of mol%. It should be noted that in the description of the glass composition range of the tellurium-based glass, the expression % refers to mol %.

[0075] TeO2 is a glass-forming component and a component that lowers the melting point of glass. The content of TeO2 is preferably 20 to 80%, particularly 40 to 75%.

[0076] Nb2O5 is a component that improves water resistance. The content of Nb2O5 is preferably 0 to 25%, 1 to 20%, and particularly 5 to 15%. If the content of Nb2O5 is too high, the viscosity of the glass increases and the fluidity tends to decrease.

[0077] The transition metal oxide is a component having laser absorption properties, and its content is preferably 0 to 40%, 5 to 30%, and particularly 15 to 25%. If the content of the transition metal oxide is too high, the devitrification resistance tends to decrease.

[0078] Among transition metal oxides, CuO has a high effect of improving laser absorption characteristics and a high effect of improving thermal stability. The content of CuO is preferably 0 to 40%, 5 to 30%, and particularly 15 to 25%. If the content of CuO is too high, the component balance of the glass composition is impaired, and the devitrification resistance tends to decrease.

[0079] In addition to the above-mentioned components, for example, the following components may be added.

[0080] Li2O, Na2O and K2O are components that reduce the devitrification resistance. Therefore, the contents of Li2O, Na2O and K2O are 0 to 5%, 0 to 3%, and particularly 0% or more and less than 1%, respectively.

[0081] MgO, CaO, SrO and BaO are components that improve the devitrification resistance and increase the softening point. Therefore, the contents of MgO, CaO, SrO and BaO are 0 to 20%, 0 to 10%, and particularly 0 to 5%, respectively.

[0082] Average particle size of glass powder D 50 The average particle size D of the glass powder is preferably less than 15 μm, 0.5 to 10 μm, and particularly 1 to 5 μm. 50 The smaller the average particle size D is, the lower the softening point of the glass powder is. 50 ” refers to the value measured on a volume basis by a laser diffraction method.

[0083] As refractory filler powder, preferably selected from one or more of cordierite, zircon, tin oxide, niobium oxide, zirconium phosphate ceramics, willemite, β-eucryptite, β-quartz solid solution, particularly preferably β-eucryptite or cordierite. These refractory filler powders have high mechanical strength in addition to low thermal expansion coefficient, and good compatibility with bismuth glass, silver phosphate glass, tellurium glass, etc.

[0084] Average particle size D of refractory filler powder 50 It is preferably less than 2 μm, particularly 0.1 μm or more and less than 1.5 μm. 50 If it is too large, the surface smoothness of the sealing material layer is likely to decrease, and the average thickness of the sealing material layer is likely to increase, resulting in a decrease in the laser sealing accuracy.

[0085] 99% particle size D of refractory filler powder 99 It is preferably less than 5 μm, 4 μm or less, and particularly 0.3 μm or more and 3 μm or less. 99 If the diameter is too large, the surface smoothness of the sealing material layer is likely to decrease, and the average thickness of the sealing material layer is likely to increase, resulting in a decrease in laser sealing accuracy. 99 ” refers to the value measured on a volume basis by a laser diffraction method.

[0086] In order to improve the laser absorption characteristics, the sealing material may further include a laser absorber, which has the effect of promoting the devitrification of the glass. If the laser absorber is further introduced, the laser absorption characteristics of the sealing material are too high, and the difference in laser absorption characteristics between the ceramic matrix and the sealing material layer is likely to become larger. Therefore, the content of the laser absorber in the sealing material layer is preferably less than 10% by volume, less than 5% by volume, less than 1% by volume, less than 0.5% by volume, and it is particularly preferred that it does not substantially contain. It should be noted that as the laser absorber, Cu-based oxides, Fe-based oxides, Cr-based oxides, Mn-based oxides and their spinel-type composite oxides can be used.

[0087] The thermal expansion coefficient of the sealing material is preferably 55×10 -7 ~110×10 -7 / ℃、60×10 -7 ~100×10 -7 / ℃, especially 65×10 -7 ~90×10 -7 / ℃. In this way, the thermal expansion coefficient of the sealing material matches the thermal expansion coefficient of the glass cover or the ceramic substrate, and the stress remaining in the sealing area becomes smaller. It should be noted that the "thermal expansion coefficient" is a value measured by a TMA (push rod thermal expansion coefficient measurement) device in the temperature range of 30 to 200℃.

[0088] The sealing material paste is usually prepared by kneading and dispersing the sealing material and the vehicle liquid using a three-roll mill, etc. As described above, the vehicle liquid contains an organic resin and a solvent. The organic resin is added for the purpose of adjusting the viscosity of the paste.

[0089] As the organic resin added to the vehicle liquid, acrylate (acrylic organic resin), ethyl cellulose, polyethylene glycol derivatives, nitrocellulose, polymethylstyrene, polyethylene carbonate, polypropylene carbonate, methacrylate, etc. As the solvent used in the vehicle liquid, N,N'-dimethylformamide (DMF), α-terpineol, higher alcohols, γ-butyrolactone (γ-BL), tetralin, terpene, butyl carbitol acetate, ethyl acetate, isoamyl acetate, diethylene glycol monoethyl ether, diethylene glycol monoethyl ether acetate, benzyl alcohol, toluene, 3-methoxy-3-methylbutanol, triethylene glycol monomethyl ether, triethylene glycol dimethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monomethyl ether, tripropylene glycol monobutyl ether, propylene carbonate, dimethyl sulfoxide (DMSO), N-methyl-2-pyrrolidone, etc. can be used.

[0090] The sealing material paste can be applied to the glass cover by a known method, such as screen printing, dispenser coating, etc. The coating film may be dried naturally, but is preferably dried in an electric furnace or a drying furnace from the viewpoint of drying efficiency.

[0091] If the dried film is subjected to a binder removal treatment by heating the entire film in an electric furnace or the like and is heated at a temperature not lower than the softening point of the glass powder to soften and flow, a sealing material layer having a high surface smoothness can be obtained.

[0092] The dried film may also be sintered by laser irradiation. In this case, it is preferred that the dried film be irradiated with laser to form a sealing material layer, and then the glass cover be heat treated at a temperature (above 100°C and below the strain point of the glass cover). In this way, the thermal shock of the glass cover is suppressed, so it is easy to prevent the glass cover from cracking.

[0093] The light absorption rate of the sealing material layer at a wavelength of 808nm and 0.005mm is preferably 50% or more, 65% or more, 70-95%, and particularly 75-85%. If the light absorption rate of the sealing material layer at a wavelength of 808nm and 0.005mm is too low, it is difficult for the sealing material layer to absorb the laser, and it is difficult for the sealing material layer to soften and flow during laser sealing. On the other hand, if the light absorption rate of the sealing material layer at a wavelength of 808nm and 0.005mm is too high, it is difficult to locally heat the ceramic substrate during laser sealing, so the reaction between the ceramic substrate and the sealing material layer cannot be fully carried out, and the laser sealing strength is easily reduced.

[0094] The average thickness of the sealing material layer is preferably less than 10.0 μm, especially not less than 1.0 μm and less than 7.0 μm. The smaller the average thickness of the sealing material layer, the less stress remaining in the sealing area after laser sealing can be reduced even if the thermal expansion coefficients of the sealing material layer, the ceramic substrate and the glass cover do not match. In addition, the accuracy of laser sealing can also be improved. It should be noted that as a method of limiting the average thickness of the sealing material layer as described above, a method of thinly applying the sealing material paste and a method of grinding the surface of the sealing material layer can be cited.

[0095] The average width of the sealing material layer is preferably less than 3500 μm, less than 1200 μm, and particularly more than 150 μm and less than 800 μm. If the average width of the sealing material layer is narrowed, the stress remaining in the sealing area can be reduced after laser sealing. In addition, the width of the frame of the ceramic substrate can be narrowed, and the effective area of ​​the airtight package that functions as a device can be expanded.

[0096] The method for manufacturing an airtight package preferably includes: a process of preparing a ceramic substrate having a base and a frame portion arranged on the base; a process of preparing a glass cover; a process of stacking the ceramic substrate and the glass cover in a manner such that the top of the frame portion of the ceramic substrate and the glass cover are in contact with a sealing material layer; and a process of irradiating a laser from the glass cover side to soften and deform the sealing material layer, thereby airtightly integrating the ceramic substrate and the glass cover to obtain an airtight package.

[0097] In the step of providing the step of laminating the ceramic base and the glass cover, the glass cover may be disposed below the ceramic base, but from the viewpoint of laser sealing efficiency, the glass cover is preferably disposed above the ceramic base.

[0098] When the ceramic substrate and the glass cover are stacked, it is preferred that the sealing material layer is placed in contact with the top of the frame of the ceramic substrate so that the sealing material layer is located on the center line in the width direction of the top of the frame of the ceramic substrate. This can improve the accuracy of laser sealing.

[0099] As the laser beam irradiated from the cover glass side, various laser beams can be used, and semiconductor lasers, YAG lasers, CO2 lasers, excimer lasers, and infrared lasers are particularly preferred from the viewpoint of easy handling.

[0100] The beam shape of the laser during laser sealing is not particularly limited. The beam shape is usually circular, elliptical, or rectangular, but may be other shapes. In addition, the beam diameter of the laser during laser sealing is preferably 0.3 to 3.5 mm.

[0101] The atmosphere for laser sealing is not particularly limited, and may be an air atmosphere or an inert atmosphere such as a nitrogen atmosphere.

[0102] The ceramic base is preferably preheated at a temperature of 100°C or higher and below the heat resistance temperature of the internal components before laser sealing. This can prevent heat conduction toward the ceramic base during laser sealing, so laser sealing can be performed efficiently.

[0103] It is preferred to perform laser sealing in a state where the glass cover is pressed, thereby promoting softening and deformation of the sealing material layer during laser sealing.

[0104] Preferably, before laminating the ceramic base and the glass cover, a step of housing the internal components in a frame of the ceramic base is further included. In this way, thermal degradation of the internal components can be suppressed.

[0105] Example

[0106] Hereinafter, the present invention will be described in detail based on examples. It should be noted that the following examples are only for illustration purposes and the present invention is not limited to the following examples in any way.

[0107] (Example 1)

[0108] First, a glass ceramic substrate (15 mm in length × 15 mm in width, 0.5 mm in base thickness, 1.0 mm in frame thickness, 60 × 10 -7 / °C, wavelength 808nm, 0.5mm-converted light absorption rate is 73%). It should be noted that the "glass ceramic" is obtained by sintering a laminated sheet of green sheets containing glass powder and refractory filler powder.

[0109] Next, a glass cover (15 mm in length×15 mm in width×0.3 mm in thickness, BDA manufactured by Nippon Electric Glass Co., Ltd.) made of alkali borosilicate glass was prepared.

[0110] In addition, a sealing material was prepared by mixing 68 volume % of bismuth-based glass powder and 32 volume % of refractory filler powder. 50 Set the particle size D to 1.0 μm and set the particle size D 99 The average particle size D of the refractory filler powder is set to 2.8 μm. 50 Set the particle size D to 1.0 μm and set the particle size D 99 The particle size is set to 2.8 μm. It should be noted that the bismuth-based glass contains Bi2O3 39%, B2O3 24.5%, ZnO 14.5%, Al2O3 1.0%, CuO 20.5%, and Fe2O3 0.5% in terms of mol%, as a glass composition. In addition, the refractory filler powder is β-eucryptite.

[0111] The thermal expansion coefficient of the obtained sealing material was measured and found to be 66×10 -7 / °C. The thermal expansion coefficient is a value measured by a push rod type TMA device, and the measurement temperature range is 30 to 200°C.

[0112] Next, along the outer peripheral edge of the glass cover, the above-mentioned sealing material is coated, dried, debonded, and sintered on the glass cover to form a sealing material layer. If described in detail, the above-mentioned sealing material, vehicle liquid and solvent are first mixed in a manner such that the viscosity becomes 90±20Pa·s (25°C, shear rate: 4), and then mixed by a three-roll mill until the powder is evenly dispersed, and paste-formed to obtain a sealing material paste. The vehicle liquid uses a vehicle liquid in which ethyl cellulose organic resin is dissolved in a glycol ether solvent. Next, on the outer peripheral edge of the glass cover, the sealing material paste is printed into a frame shape using a screen printer. Furthermore, after drying at 120°C for 10 minutes in an atmospheric atmosphere to obtain a dry film, an electric furnace is used for heat treatment, thereby debonding and sintering the dry film to form a sealing material layer having an average width of about 300μm and an average thickness of about 5μm. The light absorption rate of the sealing material layer converted to a wavelength of 808nm and 0.005mm is 75%.

[0113] Finally, the glass cover formed by sintering the sealing material layer and the glass ceramic matrix formed by dispersing the laser absorber are stacked, and the laser is irradiated from the glass cover side to soften and flow the sealing material layer, and the glass cover and the glass ceramic matrix are airtightly integrated to obtain an airtight package. It should be noted that the laser output power is 10W, the scanning speed is 15mm / second, and the beam diameter is φ500μm.

[0114] (Example 2)

[0115] An alumina ceramic substrate (15 mm in length × 15 mm in width, 0.5 mm in base thickness, 1.0 mm in frame thickness, 70 × 10 -7 / °C, wavelength 808 nm, 0.5 mm-converted light absorption rate 75%), and the laser output power was set to 16 W. An airtight package was obtained in the same manner as in Example 1.

[0116] (Comparative Example 1)

[0117] A glass ceramic substrate having a base and a frame provided on the base and not including a laser absorber (length 15 mm × width 15 mm, base thickness 0.5 mm, frame thickness 1.0 mm, thermal expansion coefficient 58 × 10 -7 / °C, wavelength 808 nm, 0.5 mm-converted light absorption rate 15%), and the laser output power was set to 14 W. An airtight package was obtained in the same manner as in Example 1.

[0118] (Comparative Example 2)

[0119] An alumina ceramic substrate (15 mm in length × 15 mm in width, 0.5 mm in base thickness, 1.0 mm in frame thickness, 69 × 10 -7 / °C, wavelength 808 nm, 0.5 mm converted light absorption rate 34%), and the laser output power was set to 19 W. An airtight package was obtained in the same manner as in Example 1.

[0120] (evaluate)

[0121] The airtight packages obtained in Example 1 and Example 2 and Comparative Example 1 and Comparative Example 2 were observed for the presence or absence of cracks, and were subjected to a temperature cycle test and a high temperature, high humidity and high pressure test.

[0122] [Table 1]

[0123] Example 1 Example 2 Comparative Example 1 Comparative Example 2 Whether there are cracks none none have have Temperature cycle test ○ ○ × × High temperature and high pressure test ○ ○ × ×

[0124] The presence or absence of cracks was evaluated by observing the vicinity of the sealing material layer of the obtained airtight package using an optical microscope.

[0125] Regarding the temperature cycle test, the obtained airtight package was After the temperature cycle was repeated under the conditions of 1000 cycles, the vicinity of the sealing material layer was observed and evaluated. Samples with no observed deterioration, cracks, peeling, etc. were evaluated as "○", and samples with observed deterioration, cracks, peeling, etc. were evaluated as "×".

[0126] Regarding the high temperature, high humidity and high pressure test: PCT (Pressure Cooker Test), the obtained airtight package is kept at 121°C, 100% humidity, 2atm, and 24 hours, and then the vicinity of the sealing material layer is observed and evaluated. Samples with no observed deterioration, cracks, peeling, etc. are evaluated as "○", and samples with observed deterioration, cracks, peeling, etc. are evaluated as "×".

[0127] As can be seen from Table 1, the evaluations of the presence or absence of cracks in the airtight packages obtained in Examples 1 and 2, the temperature cycle test, and the high temperature, high humidity, and high pressure test were good. On the other hand, the evaluations of the presence or absence of cracks in the airtight packages obtained in Comparative Examples 1 and 2, the temperature cycle test, and the high temperature, high humidity, and high pressure test were poor.

[0128] Industrial Applicability

[0129] The airtight package of the present invention is suitable for airtight packages having internal components such as sensor chips and LEDs mounted therein, and can also be suitably used for airtight packages that house piezoelectric vibration components or wavelength conversion components in which quantum dots are dispersed in organic resin.

[0130] Description of Reference Numerals

[0131] 1. Hermetic package

[0132] 10 Glass cover

[0133] 11 Ceramic substrate

[0134] 12 Base

[0135] 13 Frame

[0136] 14 Internal components

[0137] 15 Sealing material layer

[0138] 16 Top of frame

[0139] 17 Laser irradiation device

[0140] L Laser

Claims

1. An airtight package, wherein a ceramic substrate and a glass cover are airtightly integrated via a sealing material layer, characterized in that: The ceramic matrix contains 0.1 mass % to 10 mass % of a laser absorber. The difference between the light absorptivity of the ceramic substrate at a wavelength of 808 nm and a measured optical path length of 0.5 mm and the light absorptivity of the sealing material layer at a wavelength of 808 nm and a measured optical path length of 0.005 mm is 30% or less.

2. The airtight package according to claim 1, wherein: The total light reflectance of the ceramic substrate is 60% or less when the wavelength is 808 nm and the measurement optical path length is 0.5 mm.

3. The airtight package according to claim 1 or 2, characterized in that: The laser absorber contained in the ceramic matrix includes at least one selected from Fe-based oxides, Cr-based oxides, Mn-based oxides, Cu-based oxides, and spinel-type composite oxides thereof.

4. The airtight package according to claim 1 or 2, characterized in that: The ceramic matrix is ​​any one of glass ceramics, alumina, aluminum nitride or a composite material thereof.

5. The airtight package according to claim 1 or 2, characterized in that: The ceramic base has a base and a frame provided on the base, and a sealing material layer is provided between the top of the frame and the glass cover.

6. The airtight package according to claim 1 or 2, characterized in that: The sealing material layer includes bismuth-based glass and a refractory filler, and contains 0.5 volume % or less of a laser absorber, wherein the bismuth-based glass contains a transition metal oxide in the glass composition.

7. The airtight package according to claim 1 or 2, characterized in that: Internal components are housed in the frame portion of the ceramic base.